MATERIAL LOOPS POTENTIAL IN POST-DISASTER TRANSITIONAL SHELTER: LEARNING FROM 2010 MERAPI ERUPTION - Widyarko Widyarko; Khalda Fadhilah Arisya; Nisrina Dewi Salsabila; Linda Firlie Pratiwi (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2021)
Due to the geographic condition of the country, Indonesia is very vulnerable to natural disasters (BNPB, 2017). As a response, this country has various mechanisms of assistance to disaster-affected communities and assistance to fulfil basic needs for disaster victims, one of which includes the provision of ‘huntara’ as temporary shelter for the victims (BNPB, 2008). Because of its temporary nature, transitional shelters in Indonesia generally have a relatively short life cycle of building materials and may produce quite the amount of waste which would be harmful to the environment. This study attempts to understand the material life cycle process in transitional shelters built during the eruption of Mount Merapi Eruption in 2010. This study uses the approach of qualitative research with two main data collection methods—observations and interviews. This study found that the design of transitional shelter for this disaster had allowed for most of the building components to principles of Design for Disassembly, which supports the potential for material loops to occur and possibly to fulfil the characteristics of sustainable transitional shelter. However, neither the victims nor the aid providers were fully aware of this potential: thus, it could not be optimally utilised. This condition is quite unfortunate, considering that Indonesia is very prone to disasters so that transitional shelters will often be needed. Therefore, further studies are required to formulate various design standards for transitional shelter in Indonesia to optimise the potential for longevity and minimise environmental impacts.